Image-Based and Fractional-Order Control for Mechatronic Systems Theory and Applications with MATLAB® /: Theory and Applications with MATLAB®. (2020) - Copot, Cosmin; Ionescu, Clara Mihaela; Muresan, Cristina I
No abstract available